2017
DOI: 10.1016/j.bpj.2017.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Affinity Enhancement by a Conserved Flexible Linker Controls p53 Mimicry in MdmX

Abstract: MdmX contains an intramolecular binding motif that mimics the binding of the p53 tumor suppressor. This intramolecular binding motif is connected to the p53 binding domain of MdmX by a conserved flexible linker that is 85 residues long. The sequence of this flexible linker has an identity of 51% based on multiple protein sequence alignments of 52 MdmX homologs. We used polymer statistics to estimate a global K D value for p53 binding to MdmX in the presence of the flexible linker and the intramolecular binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…have mostly been used in efforts to optimize multivalent drugs through avidity (15,16). In molecular biology, effective concentrations are rarely measured experimentally, but usually estimated theoretically from the volume in which the tethered ligand is free to diffuse (17)(18)(19)(20)(21). While such simple geometric models are commonly used, they have not been tested in complex biological systems.…”
Section: Significancementioning
confidence: 99%
“…have mostly been used in efforts to optimize multivalent drugs through avidity (15,16). In molecular biology, effective concentrations are rarely measured experimentally, but usually estimated theoretically from the volume in which the tethered ligand is free to diffuse (17)(18)(19)(20)(21). While such simple geometric models are commonly used, they have not been tested in complex biological systems.…”
Section: Significancementioning
confidence: 99%
“…The linker appears to act like a mechanical element, allowing the approximation and separation of the MH1 and MH2 domains without retaining them through a long and stable compact interaction. These transitions between compact and open states are usually favored for many multidomain DNA-binding proteins (37,60,61), and in the case of Smad proteins, the expanded states could facilitate linker modification and cofactor association by providing ensembles of conformations separated by almost no energy barriers. Moreover, we observed that Smad4 is mostly monomeric (and not a trimer, as observed in crystals of MH2 domains) whereas Smad2 populates an equilibrium containing monomers, dimers and trimers, with the trimers being less abundant in full-length proteins than in the context of isolated MH2 domains.…”
Section: Discussionmentioning
confidence: 99%
“…The system is artificial, but instead estimated from polymer models. [29][30][31][32][33] The effective concentrations are sensitive to the linker sequence, 15 so without direct measurement of the effective concentrations it would be difficult to detect deviations from theoretical predictions. We thus believe that the primary strength of the present study is the ability to critically assess theoretical models of avidity in dynamic multidomain proteins.…”
Section: Discussionmentioning
confidence: 99%